Unusual case of PICC-PORT migration in the late postimplantation period - Paulić, Ivica; Mandić Paulić, Tinamarel; Aćamović Stipinović, Bojana; Stipinović, Mario (Acta Biomedica Atenei Parmensis, 2025)
Totally implantable vascular access devices provide long-term, secure venous access and are widely used among patients undergoing chemotherapy, parenteral nutrition, or those with challenging venous access. Despite standardized protocols for insertion and maintenance, complications such as catheter tip migration can occur. We report a case of secondary migration of a peripherally inserted central catheter in a male patient undergoing chemotherapy for refractory mantle cell lymphoma, attributed to high-intensity movements of the left upper extremity. Device malfunction characterized by flushing and withdrawal occlusion raised suspicion of catheter tip migration. The chest X-ray revealed the PICC, implanted via the left basilic vein, had retracted, forming a loop within the left subclavian vein. Although proximal migration can be linked to catheter-related thrombosis, this complication was caused by frequent arm movements during regular physical therapy, resembling Ratchet syndrome observed in the realm of cardiac implantable electronic devices. Due to unsuccessful repositioning attempts, the Port system was entirely removed.